Mapeamento das rotas tecnológicas descritivas dos resíduos sólidos domiciliares na Terra Indígena Trocará-PA - PASSOS, Luciane Costa dos (2025)
Solid waste management and administration are essential to prevent harm to public health and the environment. In Brazil, the challenge is even greater in rural areas and traditional communities, such as indigenous communities, where waste management is non-existent, inadequate and/or limited. The research addresses waste management in the Trocará Indigenous Land (TI), located between the municipalities of Tucuruí and Baião, in Pará, focusing on the villages and centers that make up the region. It aims to map the technological routes of household solid waste, from generation to final disposal. In this sense, the research was structured in five stages: development and application of the research instrument, compilation of information, mapping of technological routes and proposal of mitigating measures. The results indicated three scenarios regarding the final disposal of recyclable waste. The first, observed in the Ororitawa village, involves the partial use of family landfills. In the second scenario, which is predominant in the Oimotawara and Trocará villages, conventional waste collection is carried out by the Tucuruí city government, although there are difficulties related to delays in collection and inadequate burning of waste. Finally, in the third scenario, which is characteristic of the Marawytawa village and other villages, waste is discarded or burned in the open air, a deep-rooted cultural practice, aggravated by the lack of collection services. It is also revealed that, despite the implementation of family landfills, many are in disuse due to technical failures and lack of acceptance by the community. It was noted that inadequate burning of waste and open air disposal are common practices among the indigenous population analyzed, especially in the scenario of insufficient municipal services. This study reinforces the need for public policies adapted to the cultural reality of indigenous communities, in addition to environmental education programs that promote sustainability and waste management in the Trocará IT.